Mapping QTLs for anaerobic tolerance at germination and bud stages using new high density genetic map of rice - Yang, Jing; Wei, Ji; Xu, Jifen; Xiong, Yumeng; Deng, Gang; Liu, Jing; Fahad, Shah; Wang, Hongyang (Frontiers in Plant Science, 2022)
Owing to its low cost and convenience, direct seeding is becoming a popular method for rice production in many rice-growing areas. However, anaerobic conditions are a major obstacle to the direct seeding of rice and result in poor seedling establishment, which leads to yield losses. We constructed a recombinant inbred line (RIL) collection consisting of 275 lines derived from a H335 and CHA-1 cross by the single seed descent method. Via a genotyping-by-sequencing (GBS) approach, 2,498 recombination bin markers with an average physical length of 149.38 kb were obtained, and a high-density genetic map was constructed. After anaerobic treatment, 12 phenotypes related to both the coleoptile at the germination stage and seedling quality at the bud stage were evaluated. There were no significant correlations between seedling and bud traits. Genetic mapping of quantitative traits was performed for these traits across two cropping seasons. A total of 20 loci were detected, named locus 1 20. Three of them were repeatedly detected across both seasons. Six loci overlapped with those in previous reports, and nine loci were associated with multiple traits at both stages. Notably, locus 3, which is located on chromosome 2 (26,713,837 to 27,333,897 bp), was detected for both the germination and bud traits. By focusing on the locus 3 interval and by combining gene annotation and expression analyses, we identified a promising candidate gene, trehalose-6-phosphate phosphatase (OsTPP1, LOC_Os02g44230). Furthermore, RILs (G289, G379, G403, G430 and G454) that have superior phenotypes and that pyramid elite alleles were identified. The results of this study provide new genetic resources for direct-seeding rice (DSR) varieties for molecular breeding strategies and broaden our understanding of the genetic control of seedling establishment under anaerobic conditions.